2011
DOI: 10.1007/s10493-011-9505-x
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal abundance and activity of the hard tick Haemaphysalis longicornis (Acari: Ixodidae) in North China

Abstract: Seasonal abundance and activity of all the three post-embryogenic stages of Haemaphysalis longicornis, both feeding and free-living phases, were evaluated over a period of 2 years, from February 2008 to January 2010, in North China. Feeding ticks were removed weekly from head and ears of domestic sheep and the attachment sites of this tick were assessed co-instantaneously; free-living ticks were collected weekly in four habitat types by flag-dragging. The results suggested that H. longicornis mainly resides in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
33
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 53 publications
(37 citation statements)
references
References 27 publications
4
33
0
Order By: Relevance
“…Haemaphysalis longicornis is an obligate hematophagous ectoparasite widely distributed in China, New Zealand, Korea, Japan and Australia [1]. Evidence showed that H. longicornis could transmit pathogenic microorganisms, such as Babesia gibsoni , Theileria spp.…”
Section: Introductionmentioning
confidence: 99%
“…Haemaphysalis longicornis is an obligate hematophagous ectoparasite widely distributed in China, New Zealand, Korea, Japan and Australia [1]. Evidence showed that H. longicornis could transmit pathogenic microorganisms, such as Babesia gibsoni , Theileria spp.…”
Section: Introductionmentioning
confidence: 99%
“…Haemaphysalis longicornis is widely distributed in China, New Zealand, Korea, Japan, and Australia [9], and is a vector of zoonotic pathogens, including Theileria sergenti , Babesia ovata , and Rickettsia japonica [10,11], that impact negatively on human and animal health. More recently in 2009, severe fever with thrombocytopenia syndrome (SFTS) was reported in Hubei and Henan provinces of China.…”
Section: Introductionmentioning
confidence: 99%
“…It is recognized that the eggs and larvae are vulnerable to low temperature (Randolph & Storey, ; Sutherst & Bourne, ; Yoder et al ., ), so the seasonal dynamics of H. tibetensis ensure that the development of eggs and larvae occurs in relatively warm and wet months. This pattern of seasonal occurrence was also observed in Haemaphysalis longicornis (Zheng et al ., ) and Haemaphysalis concinna (Meng et al ., ).…”
Section: Discussionmentioning
confidence: 99%